The Relationship Between the Preservation of Regional Languages and the Phenomenon of Fear of Missing Out (FoMO) Among Students in Palu City - Yunidar Yunidar; Moh Tahir; Gusti Ketut Alit Suputra; Nur Halifah (STAI Hubbulwathan Duri, 2025)
The increasing dominance of global languages in digital spaces poses a threat to the preservation of regional languages, particularly among adolescents. This study examines the relationship between Fear of Missing Out (FoMO) and regional language maintenance among students at the Faculty of Teacher Training and Education (FKIP), Tadulako University. A quantitative approach was employed with a purposive sample of 200 active undergraduate students aged 17–21 years who regularly use social media platforms such as WhatsApp, Instagram, TikTok, and Twitter. Data were collected using two validated instruments: the Language Maintenance and Shift Scale (LMSS) and the FoMO Composite Scale (FMS). Descriptive statistics and Chi-Square analysis were used to examine the relationship between FoMO levels and regional language maintenance. Findings revealed a statistically significant relationship between FoMO and regional language maintenance (χ² = 93.05, p 0.01). Students with higher FoMO levels exhibited lower tendencies to maintain their regional language. Specifically, 38% of respondents with high FoMO demonstrated low language maintenance, while only 16% maintained a high level of commitment to their regional language. The results suggest that social anxiety and the need for digital connectedness contribute to the declining use of regional languages. This trend is exacerbated by the prevalence of global languages online, insufficient support from families and institutions, and a lack of cultural awareness. Efforts to preserve regional languages must involve collaborative strategies among families, educators, and policymakers to address psychosocial challenges and reframe local languages as relevant in digital and educational contexts.